Does Quality of Governance Play a Role in Trade? The Case of India’s Trade Flows - Manocha, Rinku (Asian Development Policy Review, 2022)
Economies across the globe are working towards strengthening the quality of governance to promote a conducive environment for trade and investment. The study is an attempt to empirically examine the impact of quality of governance on India’s trade with 23 Asian partners for a period from 2000 to 2019. In order to examine the determinants of India’s trade, the study employs both static as well as dynamic panel regression models. We also form an index to capture the indicators of governance using principal component analysis. The result indicates that better trade policies (trade openness) and well managed governance indicators have a positive and significant contribution on India’s trade. Sound governance definitely facilitates better institutional, administrative, and operative environment in terms of lower transaction cost, better enforcement mechanism, better channels of distribution, and reduces barriers for free movement of goods, services and capital for India.